Talent Management as a Source of Competitive Advantage - Rabbi, Faria; Ahad, Nouman; Kousar, Tahira; Ali, Tanzila (Journal of Asian Business Strategy, 2015)
In this dynamic and competitive business era organizations are facing challenges in talent management. Talent management of talented worker is becoming of great importance for the organizations which are working on global level. The demand for key position talented employees is high because those are the persons who will steer the organization and will be responsible to take the organization towards the peak of success, this is the reason organizations are in a state of fight for the best people. The major goal of every organizational strategy is to enhance the effectiveness and efficiency of the operation which could lead the organization to success. Talent Management is essential when the organizations will like to build winning teams which will be formed by talented personnel.